Calibrating Equipment for Aquatic Herbicide Application - Frederick M. Fishel (EDIS)
Calibration is the process of measuring and adjusting equipment performance. It is not difficult, but it does require some math. This 12-page fact sheet provides standard formulas and conversion factors incorporated into practical examples to help with calibration. Written by F.M. Fishel and published by the UF Department of Agronomy, July 2011.